1986
DOI: 10.1056/nejm198603203141201
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate and Cyclosporine Compared with Cyclosporine Alone for Prophylaxis of Acute Graft versus Host Disease after Marrow Transplantation for Leukemia

Abstract: We treated 93 patients who had acute nonlymphoblastic leukemia in the first remission or chronic myelocytic leukemia in the chronic phase (median age, 30 years) with high-dose cyclophosphamide and fractionated total-body irradiation, followed by infusion of marrow from an HLA-identical sibling. To evaluate postgrafting prophylaxis for graft versus host disease, we studied these patients in a sequential, prospective, randomized trial that compared the effect of a combination of methotrexate and cyclosporine (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
594
5
10

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,338 publications
(618 citation statements)
references
References 35 publications
9
594
5
10
Order By: Relevance
“…In this study, recurrence was observed in 24%, resulting in an event free survival of 54%. While follow up for the CTR-V group is more limited, these results compare favorably with the survival reported in individuals receiving unfractionated grafts [35][36][37][38][39][40][41][42][43]. Such differences may also be related to variations in the case selection, the schedule of the post-remission chemotherapy or by the considerable heterogeneity in the preconditioning in all of these studies.…”
Section: Discussionsupporting
confidence: 52%
“…In this study, recurrence was observed in 24%, resulting in an event free survival of 54%. While follow up for the CTR-V group is more limited, these results compare favorably with the survival reported in individuals receiving unfractionated grafts [35][36][37][38][39][40][41][42][43]. Such differences may also be related to variations in the case selection, the schedule of the post-remission chemotherapy or by the considerable heterogeneity in the preconditioning in all of these studies.…”
Section: Discussionsupporting
confidence: 52%
“…Clinical observations with allotransplanted patients support these findings. For example, a combination of MTX, CsA and prednisone was found to be more effective in preventing acute GVHD than the combination of CsA and prednisone alone [50][51][52], supporting the idea that MTX deletes activated T cells that have escaped from proliferation blockade by other ISD. Recent data from mice with lupus nephritis also indicate that a treatment, which combines the inhibition of T cell activation by CTLA4Ig and the induction of apoptosis in immune cells by CP, reduced renal disease and prolongs survival [53].…”
Section: Discussionmentioning
confidence: 88%
“…Fifty ml of supernatant was assayed for 51 Cr-release in a Microbeta Trilux Counter (Wallac, Germany). Maximum release was determined by incubation of target cells in 100 ml 10% SDS and spontaneous release was determined by addition of medium.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…Currently, the most common GVHD prophylaxis is based on a calcineurin inhibitor (cyclosporine [CSA] or tacrolimus [Tac]) and a short course of methotrexate (MTX, 15mg/m 2 IV on day 1, followed by 10mg/m 2 on day 3, 6, and 11). MTX, an antimetabolite and folate antagonist, has had a long history in the prevention of GVHD and in combination with a calcineurin inhibitor, is the current standard in GVHD prevention [2][3][4]. However, MTX has many associated toxicities, including severe mucositis, delayed engraftment, and renal/hepatic toxicities.…”
Section: Introductionmentioning
confidence: 99%